A new species of Ophiomegistus Banks (Acari: Paramegistidae) from Papua New Guinea - Klompen, Hans; Austin, Christopher C. (Zootaxa, 2007)
A new species of Ophiomegistus, O. spectabilis, is described from New Guinea. This represents the 13th species of this genus from New Guinea skinks. A re-evaluation of host and locality data for the genus shows a host range restricted to squamates, especially skinks, but no obvious specificity for individual skink species. Specificity for small geographical areas seems more likely.